Factors affecting child development assessed by the Ages and Stages Questionnaire (ASQ) in an Arabic speaking population. (May 2018) - Sinno, Durriyah; Tamim, Hani; Faytrouni, Farah; Mikati, Mohamad A.; Charafeddine, Lama
Highlights: This first study of an Arab population maternal education was a predictor of child development similar to western populations. In addition, gender and place of residence were found to play a role as well. Potential causes include early marital age and higher consanguinity in certain areas.